2022
DOI: 10.3390/biomedicines10102668
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Modulation in Breast Cancer

Abstract: Reactive oxygen species (ROS) are identified to control the expression and activity of various essential signaling intermediates involved in cellular proliferation, apoptosis, and differentiation. Indeed, ROS represents a double-edged sword in supporting cell survival and death. Many common pathological processes, including various cancer types and neurodegenerative diseases, are inflammation and oxidative stress triggers, or even initiate them. Keap1-Nrf2 is a master antioxidant pathway in cytoprotective mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 181 publications
(192 reference statements)
0
40
0
4
Order By: Relevance
“…For example, small molecules that block P-Rex1 function have been identified [39]. In addition, the important role of ROS in NRBP1/P-Rex1 signalling raises the possibility of targeting antioxidant pathways, such as those mediated by NRF2/KEAP1, in order to raise ROS levels above those compatible with cell survival [40]. Consequently, this newlyidentified NRBP1 signalling axis represents a potential target for precision treatment of TNBC, which urgently requires additional targeted therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…For example, small molecules that block P-Rex1 function have been identified [39]. In addition, the important role of ROS in NRBP1/P-Rex1 signalling raises the possibility of targeting antioxidant pathways, such as those mediated by NRF2/KEAP1, in order to raise ROS levels above those compatible with cell survival [40]. Consequently, this newlyidentified NRBP1 signalling axis represents a potential target for precision treatment of TNBC, which urgently requires additional targeted therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 contains 605 amino acids divided into seven domains (Neh1-7). Among them, the Neh2 domain at the N-terminal is the main regulatory domain [ 15 ]. The Neh2 domain includes seven lysine residues and two binding sites (ETGE and DLG motifs), which are the main binding sites with Keap1, and it participates in the ubiquitination regulation of Nrf2 [ 16 ].…”
Section: The Mechanisms Of Nrf2 Modulationmentioning
confidence: 99%
“…Under normal conditions, Keap1 binds to the Neh2 domain of Nrf2 in the cytoplasm and promotes ubiquitin-dependent degradation, thereby maintaining Nrf2 at low levels and preventing constitutive activation of oxidative stress [ 9 ]. Each Kelch domain of the Keap1 homodimer is linked to the Nrf2 protein by a low-affinity DLG motif and a high-affinity ETGE motif, with the former having 1/100 of the affinity of the latter [ 15 ]. The hinge and latch hypothesis proposes that the ETGE binding site acts as a hinge, while the DLG binding site acts as a latch [ 16 ].…”
Section: The Mechanisms Of Nrf2 Modulationmentioning
confidence: 99%
“…A recent study showed that the Nrf2 overexpression promotes the proliferation and migration of MCF7 and MDA-MB-231 breast cancer cells [ 6 ]. In addition, Nrf2 has been identified as a key regulator in the chemotherapeutic resistance of MCF7 cells under hypoxia conditions [ 7 ]. Considering this, targeting proteins which in turn can modulate the Nrf2-related pathway could represent a novel potential treatment for drug resistance in BC cells.…”
Section: Introductionmentioning
confidence: 99%